Electronic games as learning instruments in school Physical Education (Research, Society and Development, 2022)
This article aims to study the possibility of physical education at school to present electronic games as content to be worked on in classes, where there are several ways to be applied in classes. The BNCC understands that electronic games are a phenomenon that cannot be dissociated from the universe of children and adolescents of the new generation, as evidence they were included as general competences and specific skills in Education in Brazil. Games and games are activities based on playfulness and an extremely important part of the education of children and young people. Nowadays technology has a great influence on people's lives, becoming essential in everyone's daily life, which caused an expansion of the technologies developed. From the innovations there was an increase in the use of the internet, being active in several areas, such as education, media, politics, culture, etc. These games are influenced by the cultural or historical scenario in which they are or intend to reproduce, becoming an expression of society in addition to developing motor, social and cognitive skills. The history of virtual games is closely linked with the evolution of the internet and computing devices. Starting with the first developers and their games made in simple ways, without any projection of how these games work; with the first made to run on oscilloscopes.